1970
DOI: 10.1111/j.1600-0447.1970.tb02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Investigation of 28 Brains From Patients With Dyskinesia

Abstract: The term dyskinesia is used in different senses in the literature. Here dyskinesia (tardive dyskinesi,a) means involuntary, stereotyped, rhythmic movements. Dyskinesia may occur in all muscle groups. Most frequent and marked is a combination of dyskinetic movements of the lips, the tongue and the jaw (bucco-lingvo-masticatory dyskinesia or oral dyskinesia) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

1972
1972
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(30 citation statements)
references
References 11 publications
2
26
0
2
Order By: Relevance
“…Neuronal loss and infarction was also noted in the globus pallidum in 25% of cases. Similar findings were observed by other investigators (Nieto & Escobar, 1972;Christensen et al, 1970;Lesch & Bogerts, 1984). It is noteworthy that the distribution of the pathological lesions in schizophrenia overlap with those found in patients with postencephalitic Parkinsonism (Howard & Lees, 1987), which could explain the high incidence of schizophrenic symptoms in patients with postencephalitic Parkinsonism (Crow, 1983;Howard & Lees, 1987).…”
Section: Negative Schizophrenia Of Parkinsonismsupporting
confidence: 77%
“…Neuronal loss and infarction was also noted in the globus pallidum in 25% of cases. Similar findings were observed by other investigators (Nieto & Escobar, 1972;Christensen et al, 1970;Lesch & Bogerts, 1984). It is noteworthy that the distribution of the pathological lesions in schizophrenia overlap with those found in patients with postencephalitic Parkinsonism (Howard & Lees, 1987), which could explain the high incidence of schizophrenic symptoms in patients with postencephalitic Parkinsonism (Crow, 1983;Howard & Lees, 1987).…”
Section: Negative Schizophrenia Of Parkinsonismsupporting
confidence: 77%
“…Simiexpression induced by haloperidol is not of uniform magnitude or occurrence throughout the brain. lar processes may contribute to the caudate enlargement [60][61][62] and striatal neuropathology 63,64 which are Synaptophysin expression is usually considered to reflect synaptic density, [8][9][10][11][12][13][14][15][16][17][18] and in this respect our data observed in patients treated long-term with these drugs.…”
Section: -57mentioning
confidence: 78%
“…While some studies have noted an association between preexisting brain damage and TD, particularly in patients with aective disorders, perhaps the majority of studies have found no such correlation. Postmortem studies have been few and the positive ®ndings (nigral degeneration and increased iron deposition, midbrain gliosis, abnormal neurons in the cerebellar dentate nucleus) have yet to be replicated (Campbell et al, 1985;Arai et al, 1987;Christiansen et al, 1970). The ®ndings from in vivo neuroimaging studies have been mixed.…”
Section: Discussionmentioning
confidence: 93%